Navigating Rising Living Costs: A Qualitative Study of Financial Well-Being and Household Financial Decision-Making among Working Professionals in Uttarakhand (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Rising living costs have become a major socioeconomic challenge, placing increasing pressure on household financial stability and the financial well-being of working professionals. Although previous studies have extensively examined inflation, household finance, and financial well-being using quantitative approaches, limited attention has been paid to how individuals experience and manage rising living expenses in their everyday lives, particularly in the regional contexts of developing economies such as India. This study explored how rising living costs influence financial well-being and household financial decision-making among working professionals in Uttarakhand.The study employed an interpretivist research philosophy combined with an exploratory qualitative approach. Semi-structured interviews were carried out with 25 working professionals from government and private-sector organizations in Uttarakhand. Participants were purposefully chosen to ensure a variety of perspectives on household financial management. The interview transcripts were manually analyzed through Braun and Clarke's (2006) six-phase thematic analysis.The study showed that rising living costs have greatly affected how households plan their budgets, prioritize expenses, save money, make investment choices, and approach long-term financial planning. Participants reported increased financial stress due to higher costs for housing, healthcare, education, transportation, and other essential needs. To stay financially stable, they implemented various adaptive strategies such as stricter budgeting, cutting back on discretionary expenses, building emergency savings, and finding additional sources of income. Viewing these findings through the lens of the Family Resource Management Theory (FRMT), it becomes clear that households continuously adjust their financial resource management in response to changing economic circumstances.The study contributes to the household finance literature by extending the application of the Family Resource Management Theory to the context of rising living costs and by providing qualitative evidence from Uttarakhand, an underexplored region in India. The findings offer practical insights for policymakers, employers, financial institutions, and financial educators seeking to strengthen household financial resilience and promote sustainable financial well-being.